Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Fundraising Yayasan Dompet Dhuafa Sumatera Selatan - Aprima, Yogi; ., Maliah; Mulyani, Agus (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of training and motivation on fundraising performance of the South Sumatra Dompet Dhuafa Foundation. The research used is quantitative research method, with a population of all fundraisers of the South Sumatra Dompet Dhuafa Foundation totaling 30 fundraising people. The sample used in this study was saturated sampling technique so that 30 fundraisers were obtained. The data collection technique was carried out by observation and questionnaire. Data analysis techniques using multiple linear regression analysis, coefficient of determination, hypothesis testing t test and f test. The results of this study can be seen that the value of the multiple linear regression equation Y = 1.701 + 0.376 + 0.601 + e from the multiple linear regression equation constant value of 1.701. The results of testing the t test hypothesis of training (X_1) on Performance (Y) obtained a t test that a significant value of 0.078> alpha 0.05. This means that H_0 is accepted and H_a is rejected, it can be concluded that there is no significant influence between the training variables on the performance of the fundraising foundation of the South Sumatra Dompet Dhuafa. It is obtained from the t test that the significant value is 0.004 <0.05. This means that H_0 is rejected and H_a is accepted, it can be concluded that there is a significant influence between the motivation variable on performance in fundraising for the South Sumatra Dompet Dhuafa. From the results of the F test obtained significant 0.000 < alpha 0.05. This means that H_0 is rejected and H_a is accepted. It is concluded that there is a significant influence between training and motivation variables on the fundraising performance of the South Sumatra Dompet Dhuafa foundation.